The Merck manual of diagnosis and therapy - Moy, Daniel E.; Merck Research Laboratories (Whitehouse Station, NJ : Merck, 1999)
Presents the full-text of the "Merck Manual of Diagnosis and Therapy," Seventeenth Edition, Centennial Edition, published by Merck and Co., Inc. in Whitehouse Station, New Jersey. Offers searchable medical information.
Internet edition provided by Medical Services, USMEDSA, USHH ; Site designer and HTML author Barbara Amelia Nace ; programmer, Daniel E. Moy.
Also available in print.
Keywords: Medicine -- Handbooks, manuals, etc